2020
DOI: 10.3354/meps13463
|View full text |Cite
|
Sign up to set email alerts
|

Inter-colony foraging dynamics and breeding success relate to prey availability in a pursuit-diving seabird

Abstract: Spatial patterns of breeding seabirds are influenced by the distribution of resources in relation to the colony and the density of conspecifics from the same or adjacent colonies. We conducted an inter-colony comparison of foraging space use and behavior, diet, and reproductive success of common murres Uria aalge breeding at a large offshore and a small inshore colony on the northeastern coast of Newfoundland (Canada) during 2016-2018 under varying prey (capelin Mallotus villosus) biomass. Murres from the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…The link between fish availability and breeding success is well known in seabirds, including puffins (Cury et al., 2011; Durant et al., 2003). However, the low breeding success we observed is not simply caused by a general decrease in prey abundance near breeding grounds, which could lead to a switch to alternative prey without affecting foraging distance, as observed in other auks (Gulka et al., 2020; Ito et al., 2009). Instead, our results indicate that it is due to a combination of low prey availability near the colony, forcing birds to feed further, and a lack of suitable prey within the extended foraging range, as evidenced by birds’ higher foraging effort on longer trips, prey load composition in northern colonies (two to three times more and smaller items than in Wales), and by our diet analyses.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The link between fish availability and breeding success is well known in seabirds, including puffins (Cury et al., 2011; Durant et al., 2003). However, the low breeding success we observed is not simply caused by a general decrease in prey abundance near breeding grounds, which could lead to a switch to alternative prey without affecting foraging distance, as observed in other auks (Gulka et al., 2020; Ito et al., 2009). Instead, our results indicate that it is due to a combination of low prey availability near the colony, forcing birds to feed further, and a lack of suitable prey within the extended foraging range, as evidenced by birds’ higher foraging effort on longer trips, prey load composition in northern colonies (two to three times more and smaller items than in Wales), and by our diet analyses.…”
Section: Discussionsupporting
confidence: 48%
“…These increased breeding costs can have negative carry‐over effects on future breeding performance (Fayet, Freeman, Shoji, Kirk, et al., 2016), increase the likelihood to skip breeding (Shoji, Aris‐Brosou, et al., 2015) or lead parents to prioritise survival and abandon breeding (Erikstad et al., 2009; Wernham & Bryant, 1998). However, other studies have shown that despite having to forage further in certain conditions, auks can maintain breeding success through behavioural plasticity (Gulka et al., 2020) even while maintaining condition (Grémillet et al., 2012). Therefore, the lower breeding success associated with longer feeding distances in our study suggests that the efforts required to maintain chick‐provisioning under the conditions near some colonies exceeded the puffins’ ability or willingness to adjust their foraging behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation would be further constrained by heterogeneity in other habitat features, such as those affecting prey habitat suitability, as well as anthropogenic pressures such as fisheries activity. Moreover, there is emerging evidence that larger foraging distances may impose constraints on chick condition and subsequent breeding success, highlighting potentially important trade-offs between wider access to resources and subsequent fitness (Horswill et al 2017, Campbell et al 2019, Gulka et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Northern Gannets have a much larger foraging range than Atlantic Puffins, Black-legged Kittiwakes, and Common Murres (d 'Entremont et al 2022), so are less likely to overlap at sea with allospecifics from the same colony, but forage and raft with conspecifics at foraging hotspots (e.g., Carter et al 2016;d'Entremont et al 2022). All four species feed on capelin when it is available early in the breeding season (Hatch et al 2020;Lowther et al 2020;Ainley et al 2021;d'Entremont et al 2022), so allospecific interaction at sea with individuals from the same colony is likely during this time. When capelin complete spawning, gannets forage farther away from the breeding colony for larger fish like mackerel (d 'Entremont et al 2022), and thus are less likely to share foraging areas with the smaller seabirds later in the breeding season.…”
Section: Interactions With Conspecifics and Allospecifics At Seamentioning
confidence: 99%
“…As AIV transmission generally requires close contact between individuals or contact with contaminated environments (Ramey et al 2020), we expect that species which frequently come into contact with con-and allospecifics at the colony or at sea are more likely to contract and spread the virus. Interindividual contact is likely for species that (1) nest in high densities (e.g., Black-legged Kittiwakes;Hatch et al 2020;Lowther et al 2020;Ainley et al 2021;Careen et al Accepted). We also hypothesize that interindividual contact is likely for species that (5) scavenge or feed on other birds (e.g., Larus spp.)…”
Section: Introductionmentioning
confidence: 99%